Methotrexate Treatment in Children with Febrile Ulceronecrotic Mucha-Habermann Disease: Case Report and Literature Review - Isil Bulur; Hilal Kaya Erdoğan; Zeynep Nurhan Saracoglu; Deniz Arık (Case Reports in Dermatological Medicine)
Febrile Ulceronecrotic Mucha-Habermann disease is a rare and potentially fatal variant of pityriasis lichenoides et varioliformis acuta and is characterized by high fever, constitutional symptoms, and acute oncet of ulceronecrotic lesions. We present an 11-year-old male with Febrile Ulceronecrotic Mucha-Habermann disease who was cured with methotrexate and review the use of methotrexate for this disorder in the pediatric age group with the relevant literature.